PENINGKATAN KOMPETENSI GURU DENGAN PENGKOLABORASIAN MEDIA KONVENSIONAL DAN MODERN APLIKASI TAJWID DI BDK ACEH - Nurdin, Nurdin (Jurnal Pendidikan Ilmu Sosial, 2019)
The problems in today's learning are low competence and the lack of the ability of teachers to use media in learning and collaborating with other media. In the process of learning the Qur'an Hadith, teachers are still dominant using conventional/traditional media such as markers, blackboards, textbooks, papers, and teachers only read while students imitate so that it leads to low student learning outcomes towards mastery of recitation. This study is intended to determine the competence of teachers in utilizing learning media and collaborating between conventional/traditional media with modern applications of recitation in Balai Diklat. This study uses a qualitative approach/method with a descriptive type. The technique of data collection is by interview, observation, and documentation, while the data analysis techniques are carried out in the phase of data reduction, data presentation and conclusion drawing. The results showed that, almost all the teachers in the Al-Qur'an hadith learning material Tajwid Sciences still used conventional media. Second, teacher competency in the Education and Training Center in learning is more improved and the learning process is more interesting with the collaboration of conventional media and modern media applications of recitation science. Conclusion: Nowadays in the learning process the teacher is still dominant using conventional learning media compared to modern media, the learning process is more interesting and the results are even more increased if the teacher collaborates conventional media with modern learning media, namely the Tajwid science application.